1966
DOI: 10.1085/jgp.49.4.819
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Ion Accumulation in Muscle Cells

Abstract: A comparison is made between the quantitative predictions of equilibrium ionic distribution in living cells according to the membrane theory (Donnan equilibrium) and according to the association-induction hypothesis. This comparison shows that both theories predict competitive effects of one permeant ion on the equilibrium concentration of another permeant ion; but within the limit of experimental accuracy only the association-induction model predicts quantitatively significant specific competition of one spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
1
1

Year Published

1967
1967
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 14 publications
3
7
1
1
Order By: Relevance
“…Similar microelectrode results were obtained by Hinke (54) and McLaughlin and Hinke (55). The N M R evidence supports the theoretical and experimental work of Troshin (4, 5), Ling (6)(7)(8)(9)(10)(11)(12), and Simon (13)(14)(15), and the kinetic theory of Cope (1,53). I363…”
Section: I362supporting
confidence: 83%
See 1 more Smart Citation
“…Similar microelectrode results were obtained by Hinke (54) and McLaughlin and Hinke (55). The N M R evidence supports the theoretical and experimental work of Troshin (4, 5), Ling (6)(7)(8)(9)(10)(11)(12), and Simon (13)(14)(15), and the kinetic theory of Cope (1,53). I363…”
Section: I362supporting
confidence: 83%
“…Prior to the use of N M R , the most direct evidence for Na + complexing in tissues consisted of the equilibrium binding studies of Troshin (4,5) and Ling (12), and of cation-sensitive microelectrode studies (17,18,54,55). The equilibrium binding studies showed that equilibria of Na + between cell and solution conformed to the Langmuir absorption isotherm, with a correction for a minor fraction of Na + dissolved in intracellular water.…”
mentioning
confidence: 99%
“…[32] discussed above, indicating that Hill [2, 3] found an exception by only studying urea; (b) the fact that resting muscle cells without an intact cell membrane (EMOC preparations: see further) are able to sustain normal intracellular K + concentrations for at least two days [51]; (c) the demonstration that Artemia cysts survive for four years without energy consumption [52]; (d) reinvestigations of measurements of ionic conductivity in various cell types and of K + mobility in frog muscle cells, giving much lower values than for free K + and providing convincing explanations why some earlier studies gave high values [12, 18, 19, 22]; (e) proof that use of a K + selective electrode readily injures the cell, resulting in much too high activity measurements, so that more confidence can be given to those experimental set-ups giving low values [18, 19, 22, 64]; (f) X-ray absorption-edge fine structure determination of red blood cells giving a result that differs markedly from control measurements on a KCl solution of the same concentration [65]; (g) 39 K + NMR spectra of neurons, muscle cells and E. coli , which produced relaxation times much shorter than those of 0.1 M to 0.4 M KCl solutions and comparable to those of K + adsorbed on a Dowex-50 cation-exchange resin [66, 67, 12, 18, 19, 22]; (h) demonstration that the relationship between internal and external 42 K + concentration follows Langmuir’s adsorption isotherm, whereby real proof of adsorption was given by studying the influence of inhibitors that compete in different ways for the same adsorption sites (unlabeled Cs + and unlabeled K + ) [19, 68]. …”
Section: Introductionmentioning
confidence: 99%
“…Actin and myosin can be taken as examples of cell-matrix (NUN-) proteins [12, 14, 18, 70, 73, 134]. They possess unfolded regions [14, 75], polarize water [14, 18, 73], adsorb K + [68-73], possess cardinal adsorption sites for ATP and exhibit ATPase activity [12, 14]. It was shown that upon activation of myofibrils weak binding between the S 1 -head of myosin and actin is followed by the release of P i , allowing strong binding, which in turn leads to the power stroke and only then to ADP-release [145].…”
Section: Introductionmentioning
confidence: 99%
“…According to the current view, most of the mobile cellular K + ions are freely dissolved in free cellular water – hence they should follow the cellular water distribution. On the other hand, it has been postulated (Ling & Ochsenfeld, 1966) that the bulk of cellular K + is weakly adsorbed (not completely immobilized) to β‐ and γ‐carboxyl groups of cellular proteins; the K + distribution should follow the distribution of these side chains. The divergent views have been tested with normal K + ‐containing frog muscles and living muscles in which most of the cellular K + was (reversibly) replaced in a mole‐for‐mole fashion with the K + surrogates Rb + , Cs + or Tl + (Ling, 1977).…”
mentioning
confidence: 99%